(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The role of innovative technology in the development of education quality is significant. Innovative technologies, such as online learning platforms, virtual reality, artificial intelligence, and data analytics, play a crucial role in enhancing the quality of education. These technologies offer new and effective ways to engage students, personalize learning experiences, and provide access to a wealth of educational resources. They enable interactive and immersive learning environments, facilitate personalized instruction, and support data-driven decision-making for educators. By leveraging innovative technology, education can become more engaging, accessible, and tailored to individual needs, ultimately leading to improved learning outcomes and the overall quality of education.